Income Inequality and Income Mobility in the Scandinavian Countries Compared to the United States - Rolf Aaberge; Anders Björklund; Markus Jäntti; Mårten Palme; Peder J. Pedersen; Nina Smith; Tom Wennemo (Statistics Norway, Research Department, 1996)
This paper compares income inequality and income mobility in the Scandinavian countries and the United States during the 1980's. The results demonstrate that inequality is greater in the United States than in the Scandinavian countries and that the ranking of countries with respect to inequality remains unchanged when the accounting period of income is extended from one to 11 years. The pattern of mobility turns out to be remarkably similar despite major differences in labor market and social policies between the Scandinavian countries and the United States.
Keywords: D31; 330; Income inequality; income mobility.